Formative Evaluation of an Educational Mobile Application: an Interactive MyQiraat Application - Fitriah Ishak, Syahidatul; Mohd Zaki, Zulkifly; Anuar Mohamad, Khairul; Norazizi Sham Mohd Sayuti, M; Azim Mohd Bahrin, Muhammad; Haziana Abdul Roni, Nur; Arif Musa, Muhammad (International Journal of Engineering and Technology, 2018)
This research is concerned with deploying design pattern and formative evaluation for Qiraat mobile application using both Rapid Application Development (RAD) and User Experience (UX) methodologies. The ultimate aim of this research is to encourage ubiquitous teaching and learning of Qiraat through mobile devices. In this paper, continuous progress of MyQiraat design will be presented. The improvement of MyQiraat version design has been evaluated using high-fidelity and low-fidelity prototypes for MyQiraat version 1 and version 2 respectively. Results show that most participants realized the potential benefits of the application allowing a better understanding and encouragement of Qiraat learning among them. However, participants’ feedback should be considered in the development of the prototype.